The study of jellyfish envenomation patients at Krabi Hospital from 2010-2013 and new knowledge for reduction of its severity and mortality - ยอแสงรัตน์, วีรวัฒน์ (Disease Control Journal, 2015)
Jellyfish stings is harmful to everyone who have had contacted, there are many reports of worldwide deaths and severe envenomation from jellyfish stings. In Thailand including Krabi also have the reports of dead cases from Box jellyfish stings. In this retrospective study of jellyfish stings in Krabi Hospital which located in southern part of Thailand, we collected all cases who received first treatment of jellyfish stings in Krabi Hospital from 2010-2013. All together 62 cases, were found yearly 25 cases, 13 cases, 8 cases and 16 cases in 2010, 2011, 2012 and 2013 respectively. And as Box jellyfish stings were 10 cases, 8 cases, 4 cases and 8 cases in the above mentioned years. Initial management of Box jellyfish includes maintain basic life support if required, immediately wash the stung area at least 30 seconds with copious quantities of vinegar, do not use neither alcohol nor fresh water, avoid rubbing the stung area and gently pick off any adherent tentacles with tweezers, forceps or gloved fingers. This first aid management is new crucial for Thai people. This knowledge can reduce severity and mortality of jellyfish stings. Initial management is also presented in this study.